Prevalence of Mobile Phone Addiction among Students in Institute Technical of Kut - Sameeha Naser Abed; Rawaa Kamel Abd; Israa Dawood Salim; Nadia Abdul Razzaq Jamal (College of Nursing,University of Mosul, 2017)
Background and aim: The mobile phones have considerably the new epidemic of this century .It is a two edge sword, it has both the positive and negative consequences. The objective of this study was to determine the prevalence of mobile phone addiction among students in institute technical of Kut, and also to determine significant demographic associations. Materials and method: A descriptive cross-sectional survey was performed using a self-administered questionnaire on a sample of 380 randomly selected students. A survey was carried out in the 1st of April to the 1st of July 2017. Data analysis by using the Minitab, version 18. Results: About 66% of the students were females. The overall prevalence of mobile phone addiction was 60% in studying students (35.37% among male and 64.63% among female), with large increases in both sexes aged less or equal twenty years (59.21%). There is no significant relationship between gender and demographic characteristics and there was no any significant relationship between demographic factors ) gender, residence, marital status, and employment status) with mobile phone addiction, while was a significant association between mobile phone addiction and age groups. Conclusions: Overall female had more effects of mobile phone usage compared to male. Statistically significant difference was also observed for mobile phone addiction and age groups. There is a no significant relationship between demographic factors, gender, residence, marital status, and employment status with mobile phone use. Recommendations: The recommendations of the present study are necessary to develop a mobile phone addiction preventive measure and controlling the mobile phone use. In addition to implementing effective education and intervention strategies such as behavior modification, the promotion of healthier free-time activities, and providing a healthy living environment around youths. Counseling programs are recommended for raising awareness of families concerning mobile phone use. Keywords: Addiction , Mobile phones, Health awareness.